Modal Sosial dalam Pengembangan Ekowisata Mangrove di Desa Lontar Kabupaten Serang - Permatasari, An-Nisa; Sainah, Iin (HK-Publishing, 2024)
AbstractThis study aims to determine the social capital, obstacles and efforts of the management group and the community in overcoming the obstacles that exist in the development of mangrove ecotourism in Lontar Village. The research method chosen is descriptive qualitative, and data collection is carried out through observation, interviews and literature studies that are considered relevant to the topic raised. The results of the study show that mangrove ecotourism in Lontar Village is inseparable from the existence of a network in the development process which then grows norms, which in turn encourages the birth of social trust. Obstacles in the development of ecotourism are funds and human resources that are less competent in managing mangrove ecotourism, as well as the absence of the village government which is actually expected to help overcome these two problems. To overcome these obstacles, the tourism management group submits proposals to government agencies or institutions (outside the village) that have a high chance of being able to assist in solving the problem.Keywords: Social Capital, Barriers and Efforts, Mangrove Ecotourism Development. AbstrakPenelitian ini bertujuan untuk mengetahui modal sosial, hambatan dan upaya dari kelompok pengelola dan masyarakat dalam mengatasi hambatan yang ada pada pengembangan ekowisata mangrove di Desa Lontar. Metode penelitian yang dipilih yaitu kualitatif deskriptif, serta pengumpulan data dilakukan melalui observasi, wawancara dan studi literatur yang dianggap relevan dengan topik yang diangkat. Hasil penelitian menunjukkan ekowisata mangrove di Desa Lontar tidak terlepas dari keberadaan jaringan didalam proses pengembangannya yang kemudian menumbuhkan norma, yang selanjutnya mendorong lahirnya kepercayaan sosial. Hambatan dalam pengembangan ekowisata yaitu dana dan sumber daya manusia yang kurang kompeten dalam memanajemen ekowisata mangrove, serta ketidakhadiran pemerintah desa yang sebenarnya sangat diharapkan dapat membantu mengatasi kedua permasalahan tersebut. Untuk mengatasi hambatan tersebut, kelompok pengelola wisata mengajukan proposal kepada dinas atau lembaga pemerintah (pihak luar desa) yang berpeluang tinggi bisa membantu dalam menyelesaikan permasalahan.Kata Kunci: Modal Sosial, Hambatan dan Upaya, Pengembangan Ekowisata Mangrove.